Unicidade para equações dos tipos: Burgers, Kuramoto-Sivashinsky e Schrödinger - Zapata, Miguel Angel Cuayla (Universidade Federal de São Carlos, 2017)
Based on Carleman's estimates and under certain conditions of linear exponential decay we prove uniqueness for equations of type: Burgers, Kuramoto-Sivashinsky and Schrödinger.
Uniqueness for equations of type: Burgers, Kuramoto-Sivashinsky and Schrödinger
Keywords: Soluções; Unicidade; Equações dissipativas; Desigualdade de Carleman; CIENCIAS EXATAS E DA TERRA::MATEMATICA